Method for degrading organic matters by coupling electrochemical lithium extraction with electrooxidation of oil and gas field produced water
By using the electrochemical lithium extraction method of hydrophilic-oleophobic lithium ion sieve electrode in the oil and gas field production water, combined with the technology of electrooxidation and degradation of organic matter, the problems of poor lithium extraction and organic matter adhesion are solved, and efficient and environmentally friendly lithium extraction and organic matter degradation are achieved.
Patent Information
- Application Number
- CN202411592890.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-11-08
AI Technical Summary
Poor lithium extraction selectivity, low efficiency and organic matter adhesion problems in oil and gas fields produce water, resulting in low lithium recovery and purity and high treatment cost.
The first and second electrochemical reaction systems were constructed by using a hydrophilic-oleophobic lithium-ion sieve electrode to degrade organic matter through electrochemical extraction of lithium and coupled electrooxidation at the cathode and anode, respectively.
It has achieved high selective extraction of lithium in the water produced in complex oil and gas fields, synchronously degrades organic matter, reduces secondary pollution, and has high industrial application potential.
Smart Images

Figure CN119612707A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of oil and gas field produced water, and in particular to a method for electrochemical lithium extraction coupled with electro-oxidation degradation of organic matter in oil and gas field produced water. Background Art
[0002] Oil and gas field produced water is a byproduct of oil and gas extraction. Its composition is extremely complex, usually containing high concentrations of salts (such as sodium, potassium, calcium, magnesium and lithium), organic matter (such as petroleum hydrocarbons, fatty acids and aromatic compounds), and trace amounts of heavy metals and radioactive substances. As a potential source of lithium, oil and gas field produced water has received increasing attention in recent years. In addition, the lithium concentration in oil and gas field produced water is relatively low, accompanied by a large amount of impurity ions, which poses a huge challenge to the selective extraction of lithium.
[0003] Traditional lithium extraction technologies mainly include precipitation, solvent extraction and adsorption. These methods have been widely used to treat lithium resources in salt lake brine and ores. However, when faced with the complex system of oil and gas field produced water, they show the following shortcomings: (1) Low selectivity. Since the concentration of impurity ions in oil and gas field produced water is much higher than that of lithium ions, traditional lithium extraction technology often cannot effectively distinguish lithium ions from other metal ions, resulting in low lithium recovery rate and purity; (2) Large organic interference. Oil and gas field produced water contains a large amount of organic matter, which is easy to enrich on the adsorption material or electrode surface, resulting in the blockage of the active sites of the material and reduced adsorption efficiency. At the same time, the presence of organic matter also increases the difficulty of subsequent treatment and increases the treatment cost.
[0004] Electrochemical lithium extraction technology has received extensive attention in the field of lithium resource recovery in recent years. Electrochemical lithium extraction technology has three significant advantages: first, by adjusting the structure and electrochemical conditions of the electrode material, electrochemical lithium extraction technology can achieve selective adsorption of lithium ions and efficiently extract them from complex liquid phase systems; second, it generally does not require the introduction of organic solvents or a large amount of chemical reagents, the operation process is relatively environmentally friendly, and there are fewer by-products; third, the electrochemical process has good controllability. By adjusting parameters such as electric field strength, current density and reaction time, the adsorption and desorption process of lithium can be optimized to achieve a higher lithium extraction efficiency. Summary of the invention
[0005] The purpose of the present invention is to overcome the problems of poor lithium extraction selectivity, low efficiency and organic matter adhesion in oil and gas field produced water in the prior art, and to provide a method for electrochemical lithium extraction coupled with electro-oxidative degradation of organic matter in oil and gas field produced water. The method of electrochemical lithium extraction coupled with electro-oxidative degradation of organic matter in oil and gas field produced water of the present invention realizes the efficient extraction of lithium ions from complex oil and gas field produced water, while reducing organic matter and secondary pollution, and has high industrial application potential.
[0006] In order to achieve the above object, the present invention provides a method for electrochemical lithium extraction coupled with electro-oxidation degradation of organic matter in produced water from oil and gas fields, the method comprising the following steps:
[0007] (1) preparing a hydrophilic-oleophobic lithium ion sieve electrode: 3D printing a slurry containing a lithium ion sieve, a conductive agent, a binder and a solvent to obtain an electrode having a microchannel structure, and forming a composite film on the surface of the electrode having the microchannel structure by self-assembly of a mixed solution containing a polyelectrolyte and a fluorocarbon surfactant to obtain a hydrophilic-oleophobic lithium ion sieve electrode;
[0008] (2) Electrochemical lithium extraction coupled with electro-oxidative degradation of organic matter: constructing a first electrochemical reaction system, the first electrochemical reaction system comprising an anode, a cathode, a sealed electrolytic cell, a wire and a regulated DC power supply, wherein the cathode is the hydrophilic-oleophobic lithium ion sieve electrode prepared in step (1), and the anode is a Ti / SnO2 electrode, and the produced water from the oil and gas field is used as an electrolyte to carry out a first electrochemical reaction in the first electrochemical reaction system;
[0009] (3) Electrochemical enrichment of lithium coupled with hydrogen evolution: constructing a second electrochemical reaction system, wherein the second electrochemical reaction system comprises an anode, a cathode, a sealed electrolytic cell, a wire and a regulated DC power supply, wherein the anode is a hydrophilic-oleophobic lithium ion sieve electrode after the electrochemical reaction in step (2), and the cathode is a nickel alloy electrode, wherein a LiCl solution is used as an electrolyte to carry out a second electrochemical reaction in the second electrochemical reaction system.
[0010] Preferably, in step (1), the mass ratio of the lithium ion sieve, the conductive agent, the binder and the solvent is 1: (0.05-0.3): (0.05-0.3): (1-10).
[0011] Preferably, in step (1), the lithium ion sieve is at least one of lithium manganese oxide, lithium iron phosphate, lithium iron manganese phosphate and nickel cobalt manganese oxide.
[0012] Preferably, the conductive agent is at least one of conductive carbon black, carbon nanotubes and graphene.
[0013] Preferably, the binder is at least one of polyvinylidene fluoride, carboxymethyl cellulose, polyacrylic acid, sodium alginate and polyvinyl alcohol.
[0014] Preferably, the solvent is at least one of water, N-methylpyrrolidone, dimethyl sulfoxide, dichloromethane, toluene, ethanol and isopropanol.
[0015] Preferably, in step (1), the mass ratio of the polyelectrolyte to the fluorocarbon surfactant is (1-10):1, preferably (3-6):1.
[0016] Preferably, in step (1), the charge density of the polyelectrolyte is 0.1-5 meq / g, preferably 0.5-3 meq / g.
[0017] Preferably, the polyelectrolyte is sodium polystyrene sulfonate and / or polyallylamine hydrochloride.
[0018] Preferably, in step (1), the carbon chain of the fluorocarbon surfactant has 5-15 carbon atoms, preferably 6-12 carbon atoms.
[0019] Preferably, the fluorocarbon surfactant is sodium perfluorooctanoate and / or sodium perfluorobutyrate.
[0020] Preferably, in step (2), the conditions of the first electrochemical reaction include: voltage of 2-6 V, temperature of 20-50° C., and time of 2-10 h.
[0021] Preferably, in step (2), the pH value of the oil and gas field produced water is 8-13, the COD is 200-1200 mg / L, the chloride ion concentration is 2000-20000 mg / L, and the lithium ion concentration is 50-500 mg / L.
[0022] Preferably, in step (3), the conditions of the second electrochemical reaction include: voltage of 1.5-3V, temperature of 20-60°C, and time of 1-6h.
[0023] Preferably, the nickel alloy electrode is at least one of Ni-Co, Ni-Mo, Ni-Zn, Ni-W, Ni-Fe, Ni-Mo-Fe, Ni-Mo-Cu, Ni-Co-Zn, Ni-Mo-Co and Ni-Mo-W.
[0024] Preferably, in step (3), the pH value of the LiCl solution is 4-7, and the concentration is 10-400 mg / L.
[0025] According to the method of electrochemical lithium extraction coupled with electro-oxidative degradation of organic matter from produced water of oil and gas fields described in the present invention, the first electrochemical system constructed by using a hydrophilic / oleophobic lithium ion sieve electrode as the cathode can achieve degradation of organic matter at the anode end while extracting lithium at the cathode end. The second electrochemical system constructed by using a hydrophilic / oleophobic lithium ion sieve electrode as the anode can produce hydrogen at the cathode end while removing lithium at the anode end to achieve lithium enrichment. Among them, the anode is the hydrophilic-oleophobic lithium ion sieve electrode after the electrochemical first reaction system undergoes an electrochemical reaction. The cathode of the first electrochemical system and the anode of the second electrochemical system are used alternately and cyclically, which can achieve the cycle of lithium extraction and release and the synchronous degradation of organic matter.
[0026] Compared with the prior art, the technical solution of the present invention has the following advantages:
[0027] (1) The method of electrochemical lithium extraction and coupled electro-oxidation degradation of organic matter from produced water of oil and gas fields can achieve highly selective extraction of lithium, and is suitable for complex water bodies with low lithium concentration and high impurity ions;
[0028] (2) The method of electrochemical lithium extraction and electro-oxidation degradation of organic matter from produced water of oil and gas fields can simultaneously degrade organic matter in produced water during the process of extracting lithium, thereby reducing pollution to the environment;
[0029] (3) The method of electrochemical lithium extraction from produced water of oil and gas fields coupled with electro-oxidative degradation of organic matter will release hydrogen at the cathode during the process of releasing lithium, thereby realizing the recycling of clean energy. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is a photo of the hydrophilic-oleophobic lithium ion sieve electrode prepared in Example 1;
[0031] Figure 2 This is a picture of the contact angle of oil in air on the hydrophilic-oleophobic lithium ion sieve electrode in Example 1;
[0032] Figure 3 This is a picture of the contact angle of water on the hydrophilic-oleophobic lithium ion sieve electrode in air in Example 1;
[0033] Figure 4 This is a picture of the contact angle of oil in water on the hydrophilic-oleophobic lithium ion sieve electrode in Example 1;
[0034] Figure 5 Schematic diagram of the operation of the first electrochemical reaction system and the second electrochemical reaction system in Example 1. DETAILED DESCRIPTION
[0035] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0036] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0037] The method for electrochemical lithium extraction coupled with electro-oxidation degradation of organic matter from produced water of oil and gas fields of the present invention comprises the following steps:
[0038] (1) preparing a hydrophilic-oleophobic lithium ion sieve electrode: 3D printing a slurry containing a lithium ion sieve, a conductive agent, a binder and a solvent to obtain an electrode having a microchannel structure, and forming a composite film on the surface of the electrode having the microchannel structure by self-assembly of a mixed solution containing a polyelectrolyte and a fluorocarbon surfactant to obtain a hydrophilic-oleophobic lithium ion sieve electrode;
[0039] (2) Electrochemical lithium extraction coupled with electro-oxidative degradation of organic matter: constructing a first electrochemical reaction system, the first electrochemical reaction system comprising an anode, a cathode, a sealed electrolytic cell, a wire and a regulated DC power supply, wherein the cathode is the hydrophilic-oleophobic lithium ion sieve electrode prepared in step (1), and the anode is a Ti / SnO2 electrode, and the produced water from the oil and gas field is used as an electrolyte to carry out a first electrochemical reaction in the first electrochemical reaction system;
[0040] (3) Electrochemical enrichment of lithium coupled with hydrogen evolution: constructing a second electrochemical reaction system, wherein the second electrochemical reaction system comprises an anode, a cathode, a sealed electrolytic cell, a wire and a regulated DC power supply, wherein the anode is a hydrophilic-oleophobic lithium ion sieve electrode after the electrochemical reaction in step (2), and the cathode is a nickel alloy electrode, wherein a LiCl solution is used as an electrolyte to carry out a second electrochemical reaction in the second electrochemical reaction system.
[0041] In step (1), the mass ratio of the lithium ion sieve, the conductive agent, the binder and the solvent can be 1: (0.05-0.3): (0.05-0.3): (1-10), preferably 1: (0.1-0.25): (0.1-0.25): (3-7).
[0042] In step (1), the lithium ion sieve may be at least one of lithium manganate, lithium iron phosphate, lithium iron manganese phosphate and nickel cobalt manganese oxide. In the most preferred embodiment, the lithium ion sieve is lithium iron manganese phosphate.
[0043] In step (1), the conductive agent can be at least one of conductive carbon black, carbon nanotubes and graphene. In the most preferred embodiment, the conductive agent is a mixture of conductive carbon black and carbon nanotubes, and the mass ratio of conductive carbon black to carbon nanotubes is (3-8):1, and most preferably 6:1.
[0044] In step (1), the binder may be at least one of polyvinylidene fluoride, carboxymethyl cellulose, polyacrylic acid, sodium alginate and polyvinyl alcohol. In the most preferred embodiment, the binder is polyvinylidene fluoride.
[0045] In step (1), the solvent may be at least one of water, N-methylpyrrolidone (NMP), dimethyl sulfoxide, dichloromethane, toluene, ethanol and isopropanol. In the most preferred embodiment, the solvent is N-methylpyrrolidone.
[0046] In step (1), the mass ratio of the polyelectrolyte to the fluorocarbon surfactant may be (1-10):1, preferably (3-6):1, specifically, for example, 3:1, 3.5:1, 4:1, 4.5:1, 5:1, 5.5:1 or 6:1.
[0047] In step (1), the charge density of the polyelectrolyte may be 0.1-5 meq / g, preferably 0.5-3 meq / g, and more preferably 1-2.5 meq / g.
[0048] In step (1), the polyelectrolyte may be sodium polystyrene sulfonate and / or polyallylamine hydrochloride. In a preferred embodiment, the polyelectrolyte is sodium polystyrene sulfonate.
[0049] In step (1), the carbon number of the carbon chain of the fluorocarbon surfactant may be 5-15, preferably 6-12. Specifically, for example, it may be 6, 7, 8, 9, 10, 11 or 12.
[0050] In step (1), the fluorocarbon surfactant may be sodium perfluorooctanoate and / or sodium perfluorobutyrate. In a preferred embodiment, the fluorocarbon surfactant is sodium perfluorooctanoate.
[0051] In step (1), the conditions of the electrode having a microchannel structure may include: a height of 0.1-100 μm and a width of 0.1-100 μm.
[0052] In step (1), the electrode with a microchannel structure is further processed according to the following method: the electrode with a microchannel structure is placed in a vacuum oven for drying, and the drying conditions may include: a temperature of 55-65°C and a time of 10-24 hours; and then the electrode with a microchannel structure is placed in a hydrochloric acid solution for immersion, and the immersion conditions may include: a concentration of the hydrochloric acid solution of 0.15-0.25 mol / L and a time of 1.5-2.5 hours.
[0053] In step (1), the thickness of the composite film may be 0.01-10 nm, preferably 0.1-5 nm, and more preferably 1-3 nm.
[0054] In step (1), the surface energy of the hydrophilic / oleophobic lithium ion sieve electrode can be 1-20 mJ / m 2 , preferably 1-15mJ / m2 , more preferably 1-10 mJ / m 2 .
[0055] In step (1), the hydrophilic / oleophobic lithium ion sieve electrode is also treated by the following method: washing the hydrophilic / oleophobic lithium ion sieve with deionized water, the washing times may be one or more times, preferably multiple times; then the hydrophilic / oleophobic lithium ion sieve electrode is placed in a hydrochloric acid solution and soaked, and the soaking conditions may include: the concentration of the hydrochloric acid solution is 0.15-0.25 mol / L, and the time is 1.5-2.5h.
[0056] In step (2), the conditions of the first electrochemical reaction may include: the voltage may be 2-6V, preferably 3-5V; the temperature may be 20-50°C, preferably 30-45°C; and the time may be 2-10h, preferably 3-9h.
[0057] In step (2), the pH value of the oil and gas field produced water may be 8-13, preferably 8.5-12.5; the COD may be 200-1200 mg / L, preferably 500-1000 mg / L; the chloride ion concentration may be 2000-20000 mg / L, preferably 5000-15000 mg / L; the lithium ion concentration may be 50-500 mg / L, preferably 100-300 mg / L.
[0058] In step (2), when the lithium ion sieve is lithium iron manganese phosphate, the process of extracting lithium in the first electrochemical reaction system includes the following reactions: Li 1-x Mn y Fe 1-y PO4+Li x + +xe - →LiMn y Fe 1-y PO4.
[0059] In step (2), the organic matter degradation process of the first electrochemical reaction system includes the following reactions: organic matter + ClO·→CO2+H2O+Cl2, organic matter + ·OH→CO2+H2O. During the electrolysis reaction, the chlorine gas produced by the reaction can be passed into a NaOH solution for recovery. The method of degrading organic matter using the first electrochemical reaction system has a lower COD value, which is mainly because the ClO· free radicals produced by electrolysis of chloride ions and the ·OH free radicals produced by hydrolysis contribute to the degradation of COD.
[0060] In the present invention, the hydrophilic / oleophobic lithium ion sieve electrode has a high lithium adsorption rate and selectivity; this is mainly because the hydrophilic / oleophobic lithium ion sieve electrode contains an ultra-low surface energy interface with hydrophilic active sites, which inhibits the enrichment of organic matter on the electrode surface under the action of the electric field and reduces the embedding energy barrier of hydrated lithium ions. The SnO2 of the Ti / SnO2 electrode has high electrochemical stability and strong oxidation ability, and the titanium coating can increase conductivity and corrosion resistance, which enables the Ti / SnO2 electrode to effectively transmit current during the electrochemical reaction and remain stable in a complex water environment.
[0061] In step (3), the conditions of the second electrochemical reaction include: the voltage can be 1.5-3V, preferably 1.8-2.5V; the temperature can be 20-60°C, preferably 30-50°C; the time can be 1-6h; preferably 2-5h.
[0062] In step (3), the nickel alloy electrode may be at least one of Ni-Co, Ni-Mo, Ni-Zn, Ni-W, Ni-Fe, Ni-Mo-Fe, Ni-Mo-Cu, Ni-Co-Zn, Ni-Mo-Co and Ni-Mo-W. In the most preferred embodiment, the nickel alloy electrode is Ni-Mo. According to this preferred embodiment, the second electrochemical reaction system has a better lithium extraction effect, which is mainly due to the fact that Ni-Mo exhibits good catalytic activity in the hydrogen evolution reaction due to its porous structure and relatively large roughness factor, and has good stability in a wide pH range.
[0063] In step (3), the pH value of the LiCl solution may be 4-7, preferably 5-6; the concentration may be 10-400 mg / L, preferably 50-100 mg / L.
[0064] In step (3), when the lithium ion sieve is lithium iron manganese phosphate, the working process of the second electrochemical reaction system includes the following reactions: LiMn y Fe 1-y PO4→Li 1-x Mn y Fe 1-y PO4+Li x + +xe - ; During the cathode hydrogen evolution process, the reactions involved are: 2H + +2e - →H2.
[0065] In the present invention, preferably, the cathode of the first electrochemical reaction system and the anode of the second electrochemical reaction system are used alternately and cyclically, so as to realize the cycle of extraction and release of lithium. Figure 5 It is a schematic diagram of the working principles of the first electrochemical reaction system and the second electrochemical reaction system.
[0066] The following examples further illustrate the method for electrochemical lithium extraction coupled with electro-oxidative degradation of organic matter from produced water from oil and gas fields of the present invention. The examples are implemented on the premise of the technical solution of the present invention, and detailed implementation methods and specific operation processes are given, but the protection scope of the present invention is not limited to the following examples.
[0067] The experimental methods in the following examples, unless otherwise specified, are all conventional methods in the art. The experimental materials used in the following examples, unless otherwise specified, are all commercially available.
[0068] In the following examples and comparative examples, the testing methods of the corresponding parameters are as follows:
[0069] Determination of lithium ion concentration in electrolyte: Inductively coupled plasma atomic emission spectrometry is used for detection. The sample to be tested is pretreated and diluted to prepare a sample solution. According to the provisions of the product standard, prepare a sample solution, a blank test solution and four to five standard solutions with proportional mass concentrations, and measure the corresponding intensity values under the specified instrument conditions. Draw a standard working curve with the mass concentration of the standard solution as the horizontal axis and the corresponding intensity value as the vertical axis. Prepare the test solution and blank solution according to the provisions of the product standard, and measure at least four portions of the above test solution of the same volume. No standard solution is added to one portion, and proportional standard solutions are added to the remaining portions and diluted to the specified volume. Under the specified instrument conditions, the corresponding intensity values are measured respectively. Draw a curve with the mass concentration of the added standard solution as the horizontal axis and the corresponding intensity value as the vertical axis. Extend the curve in the opposite direction to intersect with the horizontal axis. The intersection is the mass concentration of the element to be measured. The mass fraction of the element to be measured is measured in ω and calculated according to the following formula (1):
[0070]
[0071] Where:
[0072] ρ - the value of the mass concentration of the measured element found on the curve, in grams per milliliter (g / mL);
[0073] V - the volume of the sample solution, in milliliters (mL);
[0074] m – the numerical value of the sample mass, in grams (g).
[0075] Test for chloride ion concentration in electrolyte: Detected by silver nitrate volumetric method. Take 150mL of sample and place it in a 250mL conical flask. Add 2mL of aluminum hydroxide suspension and shake evenly, filter, and discard the initial filtrate. Pipette 50mL of the treated sample and place it in a porcelain evaporating dish. Take another porcelain evaporating dish and add 50mL of pure water as a blank. Add 2 drops of phenolphthalein reagent respectively, and adjust with sulfuric acid solution or sodium hydroxide solution until the red color of the solution just fades; add 1mL of potassium chromate solution to each, and titrate with silver nitrate standard solution, while stirring with a glass rod until the solution turns orange. The chloride in the sample (as Cl - The mass concentration of (in terms of mass) is calculated according to the following formula (2):
[0076]
[0077] Where:
[0078] ρ-Chloride in water sample (as Cl - The mass concentration of the substance (measured) is in milligrams per liter (mg / L);
[0079] V0 - the volume of silver nitrate standard solution consumed in the blank test, in (mL);
[0080] V1 - the volume of silver nitrate standard solution consumed by the water sample, in (mL);
[0081] V - water sample volume, in milliliters (mL).
[0082] COD value test in electrolyte: The dichromate method is used for detection. Take 10mL of sample and place it in a conical flask. Add mercuric sulfate solution, potassium dichromate standard solution and several explosion-proof glass beads in turn and shake well. Mercuric sulfate solution is mixed according to the mass ratio of m[HgSO4]: m[Cl - ]≥20:1 ratio, the maximum amount is 2mL. Connect the conical flask to the lower end of the reflux device, slowly add 15mL of silver sulfate-sulfuric acid solution from the upper end of the condenser to prevent the escape of low-boiling organic matter, and constantly rotate the conical flask to mix it evenly. Keep the solution at a slight boiling reflux for 2h from the beginning of boiling. If it is a water-cooled device, condensed water should be passed before adding the silver sulfate-sulfuric acid solution. After reflux and cooling, add 45mL of water from the upper end of the condenser to rinse the condenser and remove the conical flask. After the solution is cooled to room temperature, add 3 drops of indicator solution and titrate with ammonium ferrous sulfate standard solution. The end point is when the color of the solution changes from yellow to blue-green to reddish brown. Record the consumed volume of ammonium ferrous sulfate standard solution. The mass concentration of chemical oxygen demand in the sample is calculated according to the following formula (3):
[0083]
[0084] Where:
[0085] C - concentration of ammonium ferrous sulfate standard solution, in moles per liter (mol / L);
[0086] V0 - the volume of ammonium ferrous sulfate standard solution consumed in the blank test, in milliliters (mL);
[0087] V1 - the volume of ammonium ferrous sulfate standard solution consumed in the water sample determination, in milliliters (mL);
[0088] V2 - the volume of the water sample taken during heating and reflux, in milliliters (mL);
[0089] f - sample dilution factor;
[0090] 8000- The molar mass is converted in mg / L.
[0091] During the testing of the above parameters, LiMn y Fe 1-y One cycle is counted as one PO4 electrode alternation. The final test results of the above parameters are LiMn y Fe 1-y The test results of PO4 electrode after 10 cycles.
[0092] Example 1
[0093] Preparation of hydrophilic / oleophobic lithium ion sieve electrodes:
[0094] (1) Lithium iron manganese phosphate powder (LiMn 0.6 Fe 0.4 PO4), a conductive carbon black-carbon nanotube mixture (the mass ratio of conductive carbon black to carbon nanotubes is 6:1), polyvinylidene fluoride and NMP in a mass ratio of 1:0.125:0.125:5 are mixed to obtain a slurry which is deposited on a carbon paper substrate by 3D printing technology, and then the obtained electrode is placed in a vacuum oven to dry for 12 h at 60 °C, and then immersed in a 0.2 mol / L hydrochloric acid solution for 2 h to obtain an electrode with a microchannel structure.
[0095] (2) A 0.5 mol / L aqueous solution of sodium polystyrene sulfonate and a 0.01 mol / L aqueous solution of sodium perfluorooctanoate were stirred and mixed to obtain a solution A. The electrode with a microchannel structure obtained in step (1) was placed in the solution A and soaked for 1 hour, then washed with deionized water for 5 times, and dried in a vacuum oven at a temperature of 60° C. to obtain a hydrophilic / oleophobic lithium ion sieve electrode A1.
[0096] The picture of hydrophilic / oleophobic lithium ion sieve electrode A1 is as follows Figure 1 As shown, the wettability of the hydrophilic / oleophobic lithium ion sieve electrode A1 was tested, and the test results are as follows:
[0097] The contact angle of oil in air on the hydrophilic-oleophobic lithium ion sieve electrode A1 is 135° (e.g. Figure 2 As shown), the contact angle of water in air to the hydrophilic-oleophobic lithium ion sieve electrode A1 is 30° (as shown Figure 3 As shown), the contact angle of oil in water on the hydrophilic-oleophobic lithium ion sieve electrode A1 is 135° (as shown Figure 4 shown).
[0098] Constructing the first electrochemical reaction system:
[0099] The hydrophilic / oleophobic lithium ion sieve electrode A1 was used as the cathode, the Ti / SnO2 electrode was used as the anode, an electrolytic cell with a volume of 100 mL was used, the electrodes were connected to a regulated DC power supply with wires, and the electrolyte was produced water from oil and gas fields. The lithium ion concentration in the produced water from oil and gas fields was 300 mg / L, the chloride ion concentration was 2000 mg / L, and the COD was 600 mg / L. The test was carried out at room temperature, the operating voltage was 5.0 V, and the system ran for 1 hour.
[0100] After taking samples of the electrolyte for analysis and testing, the results are as follows:
[0101] The lithium ion concentration is 5 mg / L, the chloride ion concentration is 2005 mg / L, and the COD value is 50 mg / L.
[0102] Constructing the second electrochemical reaction system:
[0103] The hydrophilic / oleophobic lithium ion sieve electrode A1 after the reaction of the first electrochemical reaction system was used as the anode, the cathode was made of Ni-Co alloy material, the electrolyte was 50 mg / L LiCl solution, the initial pH value was 5.5, and the lithium ion concentration in the electrolyte was 50 mg / L. The test operating voltage was 1.5 V and the reaction time was 6 h.
[0104] After sampling and analyzing the electrolyte, the lithium ion concentration in the electrolyte was 500 mg / L.
[0105] Example 2
[0106] Preparation of hydrophilic / oleophobic lithium ion sieve electrodes:
[0107] (1) Lithium iron manganese phosphate powder (LiMn 0.6 Fe 0.4PO4), a conductive carbon black-carbon nanotube mixture (the mass ratio of conductive carbon black to carbon nanotubes is 6:1), polyvinylidene fluoride and NMP in a mass ratio of 1:0.3:0.3:7 are mixed to obtain a slurry which is deposited on a carbon paper substrate by 3D printing technology, and then the obtained electrode is placed in a vacuum oven and dried for 12 h at 60 °C, and then immersed in a 0.2 mol / L hydrochloric acid solution for 2 h to obtain an electrode with a micropore structure.
[0108] (2) A 0.5 mol / L aqueous solution of sodium polystyrene sulfonate and a 0.01 mol / L aqueous solution of sodium perfluorooctanoate were stirred and mixed to obtain a solution A. The electrode with a microchannel structure obtained in step (1) was placed in the solution A and soaked for 1 hour, then washed with deionized water for 5 times, and dried in a vacuum oven at a temperature of 60° C. to obtain a hydrophilic / oleophobic lithium ion sieve electrode B1.
[0109] Constructing the first electrochemical reaction system:
[0110] The hydrophilic / oleophobic lithium ion sieve electrode B1 was used as the cathode, the Ti / SnO2 electrode was used as the anode, an electrolytic cell with a volume of 100 mL was used, the electrodes were connected to a regulated DC power supply with wires, and the electrolyte was produced water from oil and gas fields. The lithium ion concentration in the produced water from oil and gas fields was 300 mg / L, the chloride ion concentration was 2000 mg / L, and the COD was 600 mg / L. The test was carried out at room temperature, the operating voltage was 2.0 V, and the system ran for 10 hours.
[0111] After taking samples of the electrolyte for analysis and testing, the results are as follows:
[0112] The lithium ion concentration is 5.3 mg / L, the chloride ion concentration is 2002 mg / L, and the COD value is 48 mg / L.
[0113] Constructing the second electrochemical reaction system:
[0114] The hydrophilic / oleophobic lithium ion sieve electrode A1 after the reaction of the first electrochemical reaction system was used as the anode, the cathode was made of Ni-Co alloy material, the electrolyte was 50 mg / L LiCl solution, the initial pH value was 5.8, and the lithium ion concentration in the electrolyte was 50 mg / L. The test operating voltage was 3.0 V and the reaction time was 3 h.
[0115] After sampling and analyzing the electrolyte, the lithium ion concentration in the electrolyte was 488 mg / L.
[0116] Example 3
[0117] Preparation of hydrophilic / oleophobic lithium ion sieve electrodes:
[0118] (1) Lithium iron manganese phosphate powder (LiMn 0.6 Fe0.4 PO4), a conductive carbon black-carbon nanotube mixture (the mass ratio of conductive carbon black to carbon nanotubes is 6:1), polyvinylidene fluoride and NMP in a mass ratio of 1:0.2:0.2:3 are mixed to obtain a slurry which is deposited on a carbon paper substrate by 3D printing technology, and then the obtained electrode is placed in a vacuum oven to dry for 12 h at 60 °C, and then immersed in a 0.2 mol / L hydrochloric acid solution for 2 h to obtain an electrode with a microchannel structure.
[0119] (2) A 0.5 mol / L aqueous solution of sodium polystyrene sulfonate and a 0.01 mol / L aqueous solution of sodium perfluorooctanoate were stirred and mixed to obtain a solution A. The electrode with a microchannel structure obtained in step (1) was placed in the solution A and soaked for 1 hour, then washed with deionized water 5 times, and dried in a vacuum oven at a temperature of 60° C. to obtain a hydrophilic / oleophobic lithium ion sieve electrode C1.
[0120] Constructing the first electrochemical reaction system:
[0121] The hydrophilic / oleophobic lithium ion sieve electrode C1 was used as the cathode, the Ti / SnO2 electrode was used as the anode, an electrolytic cell with a volume of 100 mL was used, the electrodes were connected to a regulated DC power supply with wires, and the electrolyte was produced water from oil and gas fields. The lithium ion concentration in the produced water from oil and gas fields was 300 mg / L, the chloride ion concentration was 2000 mg / L, and the COD was 600 mg / L. The test was carried out at room temperature, the operating voltage was 5.0 V, and the system ran for 1 hour.
[0122] After taking samples of the electrolyte for analysis and testing, the results are as follows:
[0123] The lithium ion concentration is 5.5 mg / L, the chloride ion concentration is 2009 mg / L, and the COD value is 53 mg / L.
[0124] Constructing the second electrochemical reaction system:
[0125] The hydrophilic / oleophobic lithium ion sieve electrode A1 after the reaction of the first electrochemical reaction system was used as the anode, the cathode was made of Ni-Co alloy material, the electrolyte was 50 mg / L LiCl solution, the initial pH value was 5.5, and the lithium ion concentration in the electrolyte was 50 mg / L. The test operating voltage was 2.0 V and the reaction time was 1 h.
[0126] After sampling and analyzing the electrolyte, the lithium ion concentration in the electrolyte was 492 mg / L.
[0127] Example 4
[0128] The experiment was conducted according to the method of Example 1, except that the conductive carbon black-carbon nanotube mixture (the mass ratio of conductive carbon black to carbon nanotubes was 6:1) was replaced with conductive carbon black. The first electrochemical reaction system was constructed, and the electrolyte was sampled and tested after the reaction was completed. The results are as follows:
[0129] The lithium ion concentration is 16 mg / L, the chloride ion concentration is 2001 mg / L, and the COD value is 49 mg / L.
[0130] A second electrochemical reaction system was constructed, and after the reaction was completed, the electrolyte was sampled and tested. The lithium ion concentration in the electrolyte was 460 mg / L.
[0131] Example 5
[0132] The experiment was carried out according to the method of Example 1, except that polyvinylidene fluoride was replaced by polyvinyl alcohol. A first electrochemical reaction system was constructed, and after the reaction was completed, the electrolyte was sampled and tested. The results were as follows:
[0133] The lithium ion concentration is 12 mg / L, the chloride ion concentration is 1997 mg / L, and the COD value is 39 mg / L.
[0134] A second electrochemical reaction system was constructed, and after the reaction was completed, the electrolyte was sampled and tested. The lithium ion concentration in the electrolyte was 420 mg / L.
[0135] Example 6
[0136] The experiment was carried out according to the method of Example 1, except that NMP was replaced by ethanol. A first electrochemical reaction system was constructed, and after the reaction was completed, the electrolyte was sampled and tested, and the results were as follows:
[0137] The lithium ion concentration is 20 mg / L, the chloride ion concentration is 2003 mg / L, and the COD value is 46 mg / L.
[0138] A second electrochemical reaction system was constructed, and after the reaction was completed, the electrolyte was sampled and tested. The lithium ion concentration in the electrolyte was 410 mg / L.
[0139] Example 7
[0140] The experiment was carried out according to the method of Example 1, except that the Ni-Co alloy material was replaced by the Ni-Fe alloy material. A first electrochemical reaction system was constructed. After the reaction was completed, the electrolyte was sampled and tested, and the results were as follows:
[0141] The lithium ion concentration is 10 mg / L, the chloride ion concentration is 2012 mg / L, and the COD value is 41 mg / L.
[0142] A second electrochemical reaction system was constructed, and the electrolyte was sampled and tested after the reaction was completed. The lithium ion concentration in the electrolyte was 456 mg / L.
[0143] Comparative Example 1
[0144] The experiment was conducted according to the method of Example 1, except that a thin film electrode prepared by a conventional coating method was used instead of the electrode with a microchannel structure to construct the first electrochemical reaction system. After the reaction was completed, the electrolyte was sampled and tested, and the results were as follows:
[0145] The lithium ion concentration is 50 mg / L, the chloride ion concentration is 1870 mg / L, and the COD value is 30 mg / L.
[0146] A second electrochemical reaction system was constructed, and the electrolyte was sampled and tested after the reaction was completed. The lithium ion concentration in the electrolyte was 300 mg / L.
[0147] It can be seen from the results of the examples and comparative examples that the method described in the present invention can realize the cycle of lithium extraction and release and the synchronous degradation of organic pollutants in produced water of oil and gas fields.
[0148] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A method for electrochemical lithium extraction and coupled electro-oxidation degradation of organic matter from produced water from oil and gas fields, characterized in that: The method comprises the following steps: (1) preparing a hydrophilic-oleophobic lithium ion sieve electrode: 3D printing a slurry containing a lithium ion sieve, a conductive agent, a binder and a solvent to obtain an electrode having a microchannel structure, and forming a composite film on the surface of the electrode having the microchannel structure by self-assembly of a mixed solution containing a polyelectrolyte and a fluorocarbon surfactant to obtain a hydrophilic-oleophobic lithium ion sieve electrode; (2) Electrochemical lithium extraction coupled with electro-oxidative degradation of organic matter: constructing a first electrochemical reaction system, the first electrochemical reaction system comprising an anode, a cathode, a sealed electrolytic cell, a wire and a regulated DC power supply, wherein the cathode is the hydrophilic-oleophobic lithium ion sieve electrode prepared in step (1), and the anode is a Ti / SnO2 electrode, and the produced water from the oil and gas field is used as an electrolyte to carry out a first electrochemical reaction in the first electrochemical reaction system; (3) Electrochemical enrichment of lithium coupled with hydrogen evolution: constructing a second electrochemical reaction system, wherein the second electrochemical reaction system comprises an anode, a cathode, a sealed electrolytic cell, a wire and a regulated DC power supply, wherein the anode is a hydrophilic-oleophobic lithium ion sieve electrode after the electrochemical reaction in step (2), and the cathode is a nickel alloy electrode, wherein a LiCl solution is used as an electrolyte to carry out a second electrochemical reaction in the second electrochemical reaction system.
2. The method according to claim 1, characterized in that: In step (1), the mass ratio of the lithium ion sieve, the conductive agent, the binder and the solvent is 1: (0.05-0.3): (0.05-0.3): (1-10).
3. The method according to claim 1 or 2, characterized in that: In step (1), the lithium ion sieve is at least one of lithium manganese oxide, lithium iron phosphate, lithium iron manganese phosphate and nickel cobalt manganese oxide; Preferably, the conductive agent is at least one of conductive carbon black, carbon nanotubes and graphene; Preferably, the binder is at least one of polyvinylidene fluoride, carboxymethyl cellulose, polyacrylic acid, sodium alginate and polyvinyl alcohol; Preferably, the solvent is at least one of water, N-methylpyrrolidone, dimethyl sulfoxide, dichloromethane, toluene, ethanol and isopropanol.
4. The method according to claim 1, wherein in step (1), the mass ratio of the polyelectrolyte to the fluorocarbon surfactant is (1-10):1, preferably (3-6):
1.
5. The method according to claim 1 or 4, characterized in that: In step (1), the charge density of the polyelectrolyte is 0.1-5 meq / g, preferably 0.5-3 meq / g; Preferably, the polyelectrolyte is sodium polystyrene sulfonate and / or polyallylamine hydrochloride.
6. The method according to claim 1 or 4, characterized in that: In step (1), the carbon chain of the fluorocarbon surfactant has 5-15 carbon atoms, preferably 6-12 carbon atoms; Preferably, the fluorocarbon surfactant is sodium perfluorooctanoate and / or sodium perfluorobutyrate.
7. The method according to claim 1, characterized in that In step (2), the conditions of the first electrochemical reaction include: voltage of 2-6V, temperature of 20-50°C, and time of 2-10h.
8. The method according to claim 1 or 7, characterized in that: In step (2), the pH value of the produced water from the oil and gas field is 8-13, the COD is 200-1200 mg / L, the chloride ion concentration is 2000-20000 mg / L, and the lithium ion concentration is 50-500 mg / L.
9. The method according to claim 1, characterized in that: In step (3), the conditions of the second electrochemical reaction include: voltage of 1.5-3V, temperature of 20-60°C, and time of 1-6h; Preferably, the nickel alloy electrode is at least one of Ni-Co, Ni-Mo, Ni-Zn, Ni-W, Ni-Fe, Ni-Mo-Fe, Ni-Mo-Cu, Ni-Co-Zn, Ni-Mo-Co and Ni-Mo-W.
10. The method according to claim 1, characterized in that In step (3), the pH value of the LiCl solution is 4-7, and the concentration is 10-400 mg / L.
Citation Information
Patent Citations
Device and method for both electrochemical hydrogen production and lithium extraction
CN109778218A
Preparation method of underwater superoleophobic film and application of underwater superoleophobic film in lithium ion screening
CN116510354A
A lithium extraction process through decoupled electrochemical processes
WO2023228084A2
Cited By
Method for treating high-COD (Chemical Oxygen Demand) lithium-containing wastewater by electrocatalysis combined alkaline lithium extraction process
CN120664745A
Method for extracting lithium from gas field produced water based on electrochemical intercalation method
CN120683372A